Fabrication of Composite Material Based on Lignin Extracted from Sugarcane Bagasse and Modified with Chitosan for the Treatment of Methylene Blue in Aqueous Environment - Anh, Pham Ba Viet; Son, Pham Dang (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4, 2025)
A potential adsorbent material was synthesized based on the interaction between chitosan and lignin, aimed at adsorbing and treating methylene blue (MB) in aqueous environments. The highlight of this study is that the lignin was extracted from sugarcane bagasse, an agricultural by-product, aligning with green and circular economy principles. The FTIR spectroscopy analysis of the material showed the formation of bonds between chitosan and lignin, implying the successful creation of a new material - chitosan/lignin composite material. The effects of factors such as reaction temperatures, contact time, initial concentrations, and chitosan/lignin ratios on the MB adsorption of the material were investigated to evaluate the applicability of the material in dye-contaminated wastewater treatment. Experimental results indicate that the material with a chitosan/lignin ratio of 1.5/3 (mL/g) exhibited the best treatment efficiency at room temperature within 60 min. In this study, isotherm adsorption models for MB on the material were also examined. The data show that the Langmuir model better describes the adsorption process than the Freundlich model. The research findings demonstrate that the chitosan/lignin material has the capability to treat dyes in water under normal conditions, highlighting its potential application in treating textile dyeing wastewater.